Improving cognitive functions in adolescents with learning difficulties: A feasibility study on the potential use of telerehabilitation during Covid-19 pandemic in Italy. - Maggio, Maria Grazia; Foti Cuzzola, Marilena; Calatozzo, Patrizia; Marchese, Domenicaroberta; Andaloro, Adriana; Calabrò, Rocco Salvatore (Journal of Adolescence, 2021)
Introduction: Learning disabilities are due to genetic and/or neurobiological factors that alter brain functioning by affecting one or more cognitive processes related to learning. This study aimed to assess the efficacy of cognitive telerehabilitation in adolescents with learning disabilities to overcome the treatment problems related to the COVID-19 pandemic lockdown.Methods: Twenty-four patients diagnosed with Unspecified Learning Disability (mean ± SD age: 18.2 ± 2.9 years; 50% male) were enrolled in this study. The patients were assessed by a neuropsychological evaluation at the beginning and at the end of the program. All patients received cognitive treatment via a specific telehealth app to stimulate the cognitive skills related to learning. The treatment lasted four weeks, with a daily training (lasting up to 60 min), for five days a week.Results: Our young patients reported a statistically significant improvement in the main cognitive domains that are usually compromised in learning disabilities, including sustained and selective attention, shifting of attention, control of interference, memory and speed of information processing. Moreover, the patients showed a good usability and motivation during the training.Conclusions: Our study has shown that telerehabilitation could be a valid tool for the rehabilitation of specific cognitive skills in adolescents with learning difficulties.